Analysis of Disaster Management Preparedness at Ibnu Sina Hospital Makassar - Siahaan, Meilan; Hidayat, Rahmat (Omni Nursing Journal, 2025)
Background: Disasters are the trigger for the malfunctioning of health services and their facilities. For disaster handling, hospitals must be ready to handle patients in the system to support the handling process. This system is prepared by the implementation of an organizational structure when the disaster management system is activated by the hospital. Objective: To analyze disaster management preparedness at Ibnu Sina Hospital Makassar. Methods:  This descriptive study assessed 25 preparedness components, including organizational structure, team functions, operational procedures, early warning systems, and communication systems. The sample was the head of K3 emergency management. Results:  The study found that the organizational structure and team functions were 50% complete, operational procedures were only 10% complete, the early warning system was 50% complete, and the communication system was 60% complete. Gaps in operational procedures (90% incomplete) and partial readiness in other areas highlight the need for targeted improvements. Conclusion:  Overall, disaster management preparedness at Ibnu Sina Hospital Makassar remains incomplete across key components. Strengthening operational procedures, formalizing team roles, and enhancing early warning and communication systems are essential. Hospital leadership should intensify training and socialization for all disaster management team members.